2014
DOI: 10.4049/jimmunol.1302745
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Sequence Analysis of the MHC Class I G/F Segment in Common Marmoset (Callithrix jacchus)

Abstract: The common marmoset (Callithrix jacchus) is a New World monkey that is used frequently as a model for various human diseases. However, detailed knowledge about the MHC is still lacking. In this study, we sequenced and annotated a total of 854 kb of the common marmoset MHC region that corresponds to the HLA-A/G/F segment (Caja-G/F) between the Caja-G1 and RNF39 genes. The sequenced region contains 19 MHC class I genes, of which 14 are of the MHC-G (Caja-G) type, and 5 are of the MHC-F (Caja-F) type. Six putativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 27 publications
(29 reference statements)
2
23
0
1
Order By: Relevance
“…The MHC‐I alleles identified from marmosets in this study were clustered with the HLA/Patr‐G group, but the relationship was limited as shown in the phylogenetic tree (Figure ). Studies of MHC‐B/C and MHC‐G/F segments by genomic sequencing in common marmosets were described previously . In our study, novel MHC‐I alleles with full‐length sequences encoding whole proteins were identified as Caja‐G, which indicated that Caja‐G locus was predominant in the lymphocytes of those marmosets.…”
Section: Mhc Class I Alleles Detected In 12 Common Marmosetssupporting
confidence: 54%
“…The MHC‐I alleles identified from marmosets in this study were clustered with the HLA/Patr‐G group, but the relationship was limited as shown in the phylogenetic tree (Figure ). Studies of MHC‐B/C and MHC‐G/F segments by genomic sequencing in common marmosets were described previously . In our study, novel MHC‐I alleles with full‐length sequences encoding whole proteins were identified as Caja‐G, which indicated that Caja‐G locus was predominant in the lymphocytes of those marmosets.…”
Section: Mhc Class I Alleles Detected In 12 Common Marmosetssupporting
confidence: 54%
“…2a). The MHC-A region was probably formed by birth and death evolution (Piontkivska and Nei 2003) such as by repeated gene duplication and deletion events in human and non-human primates (Kono et al 2014;Shiina et al 2006) as shown in the detailed segmental and phylogenetic sequence analysis of the rhesus macaque MHC alpha block ). In the HLA-A region, an approximately 70 kb insertion and 50 kb deletion near the HLA-A gene were detected in some HLA-A allele lineages (Watanabe et al 1997).…”
Section: Discussionmentioning
confidence: 97%
“…In addition, two large segments of the marmoset MHC class I region have been sequenced. The G/F segment corresponds to the part of the HLA complex containing the HLA‐A , HLA‐F , and HLA ‐ G genes and has 14 genes related to HLA‐G and five related to HLA‐F , but none corresponding to HLA‐A . The B/C segment corresponds to the part of the HLA complex containing the HLA‐B and ‐C genes and contains nine Caja‐B genes, five of which appear functional .…”
Section: Kir Genes Of Catarrhine and Platyrrhine Primates Are More DImentioning
confidence: 99%